Characteristics of recovery and resilience in the Romanian regions - József BENEDEK (Eastern Journal of European Studies, 2017)
Differences in regional economic growth trajectories and the multiple regional effects of the economic crisis have revived studies dedicated to the subject of resilience. The main goal of this paper is to measure the resilience of the Romanian regions, seeking to answer two basic questions: What was the regional impact of the global crisis from 2008 onwards? How have the Romanian regions recovered following the crisis? We focus our analysis on the region with the highest economic growth in the post-crisis period (South-East) in order to understand the main drivers of economic recovery. The methodology of the study involves a multi-dimensional understanding of resilience. This means that we have extended our focus from economic indicators towards a more inclusive methodology related to the measurement of regional well-being. Our main finding is that productivity growth was a critical driver of economic recovery, having a significant impact on income and jobs, as well as influencing non-material elements of well-being.